Students' problem solving appraisal and behaviour in asynchronous online discussion forum - Ariff, Noor Izzati (Innovative Teaching and Learning Journal, 2017)
This study is intended to identify student problem-solving appraisal and their problem-solving behaviour in asynchronous online discussion forums (AODF). Thirty students enrolled in Authoring Language (AL) participated in this study. This study intends to explore the relationship between students’ problem-solving appraisal in AODF with their actual AODF behaviour, and to determine whether there is any correlation between their academic performance of AL course. This study involved quantitative and qualitative data collection. Problem Solving Inventory (PSI) and students’ AODF transcripts were used as research instruments. Also, students’ performance scores of the AL course were gathered as part of the data for this research. The findings have revealed that a high PSI score reflects positive problem-solving skills, with an average PSI score being 97.43. The most dominant problem-solving behaviour in AODF is ‘providing information’ behaviour. Students’ problem-solving behaviour in AODF has been decreasing across time, and there is a moderately significant correlation between the PSI score and total marks for the AL course (r=0.449, p<0.05). The findings of this study may provide instructors with detailed information about students’ problem-solving appraisal and problem-solving behaviour in AODF and their impact on students’ academic performance.